A Prospective Randomized Clinical Study to Assess and Compare the Efficacy of Ultrasound Guided Quadratus Lumborum Block versus Transversus Abdominis Plane Block for Postoperative Analgesia in Patients Undergoing Abdominal Hysterectomy Under General Anaesthesia - Arvind Khare; Beena Thada; Mudrika Parasrampuria; Kuldeep Jonwal; Mukut Rathore (Indian Journal of Pain)
Background and Aims: Multimodal analgesia regimens for optimizing the postoperative pain following abdominal surgeries are a crucial component of enhanced recovery after surgery (ERAS), as it reduces postoperative opioid consumption along with their adverse effects. We compared the analgesic efficacy of ultrasound-guided transmuscular quadratus lumborum block (QLB) versus posterior transversus abdominis plane block (TAPB) with respect to duration of analgesia, modified Defense and Veterans Pain Rating Scale (DVPRS) scores for pain, activity, sleep, stress, and mood, respectively, the total amount of rescue analgesic consumption, hemodynamics parameters and side effects, in patients undergoing total abdominal hysterectomy under general anesthesia. Materials and Methods: In this study, which was prospective, randomized, and double-blind, 60 patients of the American Society of Anesthesiologists Physical Status I and II, aged 18–65 years, undergoing abdominal hysterectomy, were randomized into two groups. Group QLB (n = 30) and Group TAPB (n = 30) received bilateral QLB and TAPB with 40 ml of 0.375% ropivacaine, respectively. The data were compared using standard qualitative and quantitative tests. Results: The duration of pain relief was longer in Group QLB compared to Group TAPB (981.83 ± 138.62 min vs. 637 ± 127.02 min, P < 0.0001). The DVPRS score for pain, activity, sleep, stress, and mood, respectively, were significantly lower in Group QLB (P < 0.05). The total rescue analgesic consumption was significantly lesser in Group QLB (103.33 ± 18.26 mg) compared to Group TAPB (150.00 ± 50.85 mg) (P < 0.0001). No significant hemodynamic changes or side effects were observed (P > 0.05). Conclusion: Bilateral QLB significantly prolonged the duration of analgesia with reduced rescue analgesic requirement compared with bilateral TAPB in patients undergoing total abdominal hysterectomy.